Estudio de factibilidad para la creación de una empresa productora y comercializadora de helados de cóctel preparados con nitrógeno líquido en la ciudad de Bogotá (2018)
This feasibility study for a new maker and distributor cocktail ice cream startup. Cocktail ice cream will be prepared with liquid nitrogen, it will start at Bogota, this study was possible thanks to opportunities identified into food and ice cream sector. Additionally, we observed new changes food trends, because persons look for to feed healthy, some persons avoid to feed with unhealthy food or exposure their body to chemicals, colorants and artificial flavors. We elaborate a market study in which we search an ideal demand for cocktail ice cream, at the same time, we identify some persons needs, in this way, we create strategies to call new customers.